2009
DOI: 10.1073/pnas.0906775106
|View full text |Cite
|
Sign up to set email alerts
|

Intact signal peptide of CD18, the β-subunit of β 2 -integrins, renders ruminants susceptible to Mannheimia haemolytica leukotoxin

Abstract: Signal peptides of membrane proteins are cleaved by endoplasmic reticulum-resident signal peptidase, and thus, are not present on mature membrane proteins. Here, we report that, contrary to the paradigm, the signal peptide of ruminant CD18, the ␤-subunit of ␤2-integrins, is not cleaved. Intriguingly, the intact signal peptide of CD18 is responsible for the susceptibility of ruminant leukocytes to Mannheimia (Pasteurella) haemolytica leukotoxin (Lkt). Inhibition of Lkt-induced cytolysis of ruminant leukocytes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…Bovine CD18 retains the signal peptide due to a glutamine residue at position Ϫ5. Replacement of glutamine with glycine at position Ϫ5 in the bovine protein restores signal peptide cleavage (26). Bovine CD18 remains associated with the cell due to a transmembrane region.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine CD18 retains the signal peptide due to a glutamine residue at position Ϫ5. Replacement of glutamine with glycine at position Ϫ5 in the bovine protein restores signal peptide cleavage (26). Bovine CD18 remains associated with the cell due to a transmembrane region.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that leukotoxin binds to amino acids 5-17 of the signal peptide of ruminant CD18, the β subunit of β 2 integrins, which, contrary to its paradigmatic cleavage in nonruminants, remains uncleaved and intact on mature CD18 molecules expressed on the cell surface of ruminant leukocytes (10). Furthermore, our studies revealed that the signal peptide sequence of ruminant CD18 contains cleavage-inhibiting glutamine (Q), whereas that of nonruminants contains cleavage-inducing glycine (G) at amino acid position 18, which is position 5 upstream of the cleavage site.…”
mentioning
confidence: 99%
“…Furthermore, our studies revealed that the signal peptide sequence of ruminant CD18 contains cleavage-inhibiting glutamine (Q), whereas that of nonruminants contains cleavage-inducing glycine (G) at amino acid position 18, which is position 5 upstream of the cleavage site. Sitedirected mutagenesis leading to the substitution of Q with G at amino acid position -5 resulted in the cleavage of the signal peptide and abrogation of leukotoxin-induced cytolysis of target cells (10), revealing an approach to genetically engineer cattle that will produce leukocytes resistant to leukotoxin via the expression of signal peptide-less CD18 on their surface. In this proof-of-principle study demonstrating the utility of this approach, we used precise gene editing to modify both alleles of CD18 to create bovine fetal fibroblasts bearing the Q(-5)G substitution and somatic nuclear transfer to clone a bovine fetus producing leukocytes that express signal peptide-less CD18 on their surface.…”
mentioning
confidence: 99%
“…The acylated LKT then binds the CD18 chain of the ␤ 2 -integrin lymphocyte function-associated antigen 1 (LFA-1) (3, 21-26, 33, 40, 41, 44, 55, 63) on ruminant leukocytes. LKT binding to amino acids 5 to 17 of the signal sequence of CD18 is required for cell death and restricts cytotoxicity to ruminant leukocytes, because the signal sequence for CD18 is not present on mature leukocytes from other mammalian species (55). Other investigators have shown that both the pro-form and mature LKT are capable of binding CD18, although the pro-LKT does not cause cytotoxicity (62).…”
mentioning
confidence: 99%